Agricultural Education for Sustainable Rural Development in Developing Countries – Challenges and Policy Options - Jhansi Seetharam Chittoor; Santosh Kumar Mishra (Journal of Education and Learning (EduLearn), 2012)
Governments all over the world have focused upon sustainable rural development in an organized way. Rural locations, in particular, need more economic development in order to match urban centric development. Poverty in rural areas has remained by and large, the main focal point of governments and development agencies. Sustainable rural development is the most effective way to eliminate this curse. Environment friendly growth stimulators have been provided to rural populations. This paper aims to: (a) give an insight into the linkages between the agricultural education and sustainable rural development, and (b) present strategies for sustainable rural development. Challenges in sustainable rural development for developing countries in the 21st century have also been looked into. The paper concludes that agricultural education institutions in developing countries will need to address not only immediate production needs, but also long-term food security, sustainable agriculture and rural development needs.